Highlighting Traffic Accidents on Roundabouts Using MRSS-AHP Expert System - Ghassan Suleiman; Mohammad K. Younes; Murat Ergun; M. F. Abushammala; Mohammad Aljaradin (Civil Engineering Journal, 2024)
The frequency and severity of traffic accidents are causing growing concern. This study aims to develop a tool to improve the traffic safety level on roundabouts and identify the influence of traffic operations, geometric parameters, weather, and time of day on improving roundabout traffic safety. It is the first study to evaluate the performance of the integrated Median Ranked Set Sample (MRSS) and Analytic Hierarchy Process (AHP) with statistical analysis. A hierarchy tree of accident causes has been developed using data gathered from accident reports and relevant authorities. Then, the selected stakeholders’ professionals prioritized the traffic accident causes using a MRSS and AHP. Moreover, traffic microsimulation software VISSIM was also used to extract traffic operation parameters for the analysis. Afterwards, Analysis of Variance (ANOVA) was used to validate the causes of traffic accidents. The results show that geometric design accounts for 36% of accidents at roundabouts, followed by traffic operation (22%). However, conflicting and queuing lengths are responsible for about 20% of traffic accidents. The tools developed, and the causes of accidents determined in this study will help geometric designers and city planners to take the necessary measures to minimize accidents and enhance traffic safety levels in urban areas. Doi: 10.28991/CEJ-2024-010-04-013 Full Text: PDF